2021
DOI: 10.1177/0003319720987739
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Biomarkers Associated With Long-Term Incidence of Symptomatic Peripheral Arterial Disease and Mortality

Abstract: We evaluated if plasma biomarkers can predict incident peripheral arterial disease (PAD) and mortality in a longitudinal cohort study. Men (n = 3618) and women (n = 1542) were included in the Malmö Preventive Project and underwent analysis of: C-terminal endothelin-1 (CT-proET-1), N-Terminal prosomatostatin (NT-proSST), midregional proatrial natriuretic peptide (MR-proANP), procalcitonin (PCT), and copeptin. Participants were followed up for incident PAD and mortality until December 31, 2016. Median follow-up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…A substantial subset of circulating biomarkers—C-terminal endothelin-1 (CT-proET-1), N-terminal prosomatostatin ([NT-proSST), midregional proatrial natriuretic peptide (MR-proANP), procalcitonin (PCT), and copeptin—were prospectively evaluated for their role in PAD development and mortality in 3618 men and 1542 women in the Malmö Preventive Project [ 75 ]. Increased levels of CT-proET-1, NT-proSST, and MR-proANP were independently associated with incident PAD, whereas all the vasoactive biomarkers were independently associated with mortality during the 11-year follow-up [ 75 ].…”
Section: Differences In Circulating Biomarkers Of Pad and Chdmentioning
confidence: 99%
“…A substantial subset of circulating biomarkers—C-terminal endothelin-1 (CT-proET-1), N-terminal prosomatostatin ([NT-proSST), midregional proatrial natriuretic peptide (MR-proANP), procalcitonin (PCT), and copeptin—were prospectively evaluated for their role in PAD development and mortality in 3618 men and 1542 women in the Malmö Preventive Project [ 75 ]. Increased levels of CT-proET-1, NT-proSST, and MR-proANP were independently associated with incident PAD, whereas all the vasoactive biomarkers were independently associated with mortality during the 11-year follow-up [ 75 ].…”
Section: Differences In Circulating Biomarkers Of Pad and Chdmentioning
confidence: 99%
“… 10 , 11 Regarding population-based studies, CT-proET-1 was recently shown to be associated with all-cause mortality in a Swedish population. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of peripheral artery disease (PAD) includes an inflammatory, atherosclerotic and hypercoagulable state involving vascular endothelial cells, vascular smooth muscle cells and inflammatory cells [44]. Biomarkers can be used to evaluate different stages of this process caused by endothelial and macrovascular dysfunction [44]. It is of potential relevance to assess the role of endocan in patients with PAD (e.g.…”
Section: Endocan and Peripheral Artery Diseasementioning
confidence: 99%